Mechanical Characteristic and Energy Absorption Behavior of Closed-Cell Pure and A356 Alloyed Aluminum Foams during Compression - Fadhil, Hayder A.; Laftah, Rafil M.; Abdulwahab, Qussay T. (Basrah Journal for Engineering Sciences, 2024)
The goal of this study is to evaluate the mechanical characteristics and energy absorption capabilities of both closed-cell pure Aluminum foam and closed-cell A356 foam. A portion of the lightweight pure foam samples (17.12, 17.77 and 15.27 g) is produced through casting of raw material (99.9 % pure aluminum) using Titanium Hydride (TiH 2 ) as a foaming agent, which lead to (7.5, 7 and 8) Pores Per Inches (PPI); and samples of A356 foam (38.24, 38.18 and 35.88 g) is produced through casting of A356 alloyed material with same procedure which lead to (11, 10 and 12) PPI. In order to determine the maximum compressive strength, strength-to-weight ratio, energy absorption density, complementary energy, and energy absorption efficiency, a uniaxial compression test is conducted. The results indicate that compression of pure foam structure smashed in a ductile manner and shows a lamellar eutectic structure while A365 foams under compression are crashed with brittle character with complex phases distribution inside (polyhedral and globular morphologies), A noticeable enhancement is observed in the mechanical characteristics of the A356 foam. The maximum compressive strength and specific energy absorption of alloyed foam are increased by a factor nearly of 4 and 2 respectively for all tested samples. Also, the result shows a significant decreasing in compressive strength with increasing of PPI for both pure and alloyed foam. The notable enhancements in the properties of alloyed closed cell foam render these advanced materials a viable option for high-strength applications.